PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA PERUSAHAAN DENGAN STRATEGI BISNIS SEBAGAI VARIABEL INTERVENING : STUDI PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA - Junita, Dewi; Sari, Ria Nelly; Kurnia, Pipin (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This research uses contingency theory to examine the influence of managementcontrol system (SPM) on company performance, management control system (SPM)to business strategy, business strategy to company performance, and managementcontrol system (SPM) to company performance with business strategy asintervening variable . The research used data collection method of mail survey andcensus sampling to manufacturing company represented by Chief Financial Officer(CFO) or subordinated manager, internal auditor and controller of manufacturingcompany listed in Indonesia Stock Exchange (BEI). The data obtained wereanalyzed by using PLS analysis technique (Partial Least Square) through WarpPLSsoftware. In addition, to test the fourth hypothesis, the VAF method is used to testthe intervening variables in the hypothesis. The results showed that themanagement control system is directly and positively related to the companysperformance. Furthermore, the management control system has a positive effect onbusiness strategy. Then, business strategy is also influential and positive on theperformance of the company. The results of this study also shows that themanagement control system has a positive effect on the companys performancethrough business strategy with business strategy as a partial mediator.